2017
DOI: 10.1021/acs.energyfuels.6b02799
|View full text |Cite
|
Sign up to set email alerts
|

Efect of Temperature on the Flow Profile of the Bio-oil Produced from the Fast Pyrolysis of Sisal Residue

Abstract: The objective of this study was to evaluate the flow of a film of bio-oil in a cylindrical tube similar to the tube of a heat exchanger found in a fast pyrolysis unit of sisal residue in a fluidized bed. The velocity profile of bio-oil was determined from the momentum balance and the equation that describes the rheological behavior of the fluid. The rheological behavior of bio-oil was determined at 60, 70, 80, 90, and 110 °C, and eight models to describe the rheological behavior were evaluated. The Sisko, Hers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…Fast pyrolysis of eucalyptus was carried out in the same pilot plant, under similar operating conditions as the sisal residue tests (N 2 F = 11 N m 3 /h; BioF = 1083 g/h and temp = 500 °C), and the results showed that the viscosity values of the eucalyptus bio-oil are about 10 times smaller than those coming from the sisal residue (Appendix A, Supporting Information), being close to those found by other authors. Figure shows that the viscosity of sisal residue bio-oil decreases with increasing shear rate, which confirms the yield-pseudoplastic rheological behavior of this fluid, as reported in the work of Pereira and Pires . It has also been observed that viscosity is influenced by temperature, and, as discussed above, the values obtained are comparable to those of other bio-oils at temperatures above 70 °C.…”
Section: Resultscontrasting
confidence: 59%
See 4 more Smart Citations
“…Fast pyrolysis of eucalyptus was carried out in the same pilot plant, under similar operating conditions as the sisal residue tests (N 2 F = 11 N m 3 /h; BioF = 1083 g/h and temp = 500 °C), and the results showed that the viscosity values of the eucalyptus bio-oil are about 10 times smaller than those coming from the sisal residue (Appendix A, Supporting Information), being close to those found by other authors. Figure shows that the viscosity of sisal residue bio-oil decreases with increasing shear rate, which confirms the yield-pseudoplastic rheological behavior of this fluid, as reported in the work of Pereira and Pires . It has also been observed that viscosity is influenced by temperature, and, as discussed above, the values obtained are comparable to those of other bio-oils at temperatures above 70 °C.…”
Section: Resultscontrasting
confidence: 59%
“…Some tests were carried out to produce 4 additional bio-oil samples under different operating conditions. The results (Appendix A, Supporting Information) showed that the water contents of the bio-oil samples are influenced by the operational conditions of production, although the variation between the samples is small and the water content is close to the value reported by Pereira and Pires (biomass = 6.11 wt %; bio-oil = 5.18 wt %). This fact reinforces that smaller flow rates of drag gas were responsible for the production of a bio-oil with lower viscosity due to the increase in the residence time of the molecules in the reactor, causing the reduction of their size.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations